Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia - Patoleta, Barbara; Gardzińska, Joanna (Zootaxa, 2013)
The monotypic jumping spider genus Lystrocteisa Simon, 1884 is redescribed. A new generic diagnosis is provided, based on both sexes, together with redescriptions of the male and description and illustration of the hitherto unknown female of the type species.